(untitled) (Nepal Journal of Epidemiology, 2014)
Background Needle phobia, clinically termed as Belonephobia strongly influences psychological behaviors. Physiological responses include palpitations, shortness of breath, nervousness and fainting. In Nepal, first year MBBS students prick their own finger for hematology practical. They use to suffer from Belonephobia and pain due to finger prick. The main objective of this study was to determine influential fear factors and assessment of pain during hematology practical. Material and Methods: One hundred and forty two first year medical students of basic sciences participated in the study. Standard pricking was performed by blood lancet in the middle and side of the middle finger during hematology practical for the assessment of pain in Young Baker scale and visually rating scale. They also responded to a questionnaire on factors associated with fear of needles and lancets, symptoms etc. Results: Out of 142 students, numbers of males were 76 and females were 66. Belonephobia persisted among 65.2% females and 42.1% males, p<0.01. Watching others during lancing or receiving injection was a significant fear factor. Lateral side pricking was preferred by students for less pain. Mild, moderate, “hurts little bit”, “little more”, “even more” were the maximum response for pain sensation. Conclusion: Positive approaches like separation of lancing area, systematic exposure, behavioral therapy, counseling and administration of anti-anxiety drugs for severely needle phobics, can alleviate fear and anxiety. Female students need more assistance. Development of proper strategies and necessary interventions are required, which will facilitate to overcome this phobia. DOI: http://dx.doi.org/10.3126/nje.v4i5.12024 Nepal Journal of Epidemiology 2014; 4(5):433-40